Bioremediation of petroleum sludge was conducted by using land-farming method in micro scale and by applying an indigenous bacteria Bacillus megaterium. The samples were from PT. Pertamina Musi Banyuasin district of South Sumatra. The research aim was to evaluate the performance of the bacteria in degrading petroleum sludge. The rate of the biodegradation process was determined by using differential method and the data analyses show that the reaction order is 0.74. Then, the rate of biodegradati - BAMBANG YUDONO; MUHAMMAD SAID; . SABARUDDIN; ADIPATI NAPOLEON; MARYATI BUDI UTAMI (Bogor Agricultural University, Indonesia, 2010)
Bioremediation of petroleum sludge was conducted by using land-farming method in micro scale and by applying an indigenous bacteria Bacillus megaterium. The samples were from PT. Pertamina Musi Banyuasin district of South Sumatra. The research aim was to evaluate the performance of the bacteria in degrading petroleum sludge. The rate of the biodegradation process was determined by using differential method and the data analyses show that the reaction order is 0.74. Then, the rate of biodegradation constant was determined by using an integral method assuming that the biodegradation process was a first reaction order. From the calculation, it was revealed that the biodegradation reaction constant was 0.0204/day. The bioremediation-kinetics model is y = -0.0204X + 2.0365, and by using this model the bioremediation process could be ended after 99.83 days. The qualitative analysis was carried out by using GC-MS to investigate the components of compounds changed during the bioremediation process. The results show that the B. megaterium could degrade 99.32% of alkane compounds.